2002
DOI: 10.1046/j.1365-2893.2002.00350.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for intrafamilial transmission of hepatitis C virus in Karachi, Pakistan

Abstract: Household contacts of hepatitis C virus (HCV)-positive patients are considered at increased risk of HCV infection. This cross-sectional study during April through June 1999 assessed the prevalence and risk behaviours associated with HCV seropositivity among the household contacts of HCV seropositive thalassaemic children in Karachi, Pakistan. Among the 341 household contacts of 86 thalassaemic HCV seropositive children who were tested, 70 (20.5%) were positive for anti-HCV antibodies. The stratified analysis s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 40 publications
4
31
0
1
Order By: Relevance
“…A number of studies have reported an intrafamilial spread of HCV to be five-to tenfold higher in individuals living with an HCV infected person as compared to the general population. Other than sexual contacts, nonsexual risk factors include mother to child exposure at birth and some behavioral attitudes at risk such as sharing of toothbrush, blades, and razors [Ackerman et al, 2000;Akhtar et al, 2002;Memon and Memon, 2002;Mast, 2004]. Other reports, in contrast, suggested a very low extent for intrafamilial transmission of HCV [Kim et al, 1998;Saltoglu et al, 1998;Keiserman et al, 2003].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have reported an intrafamilial spread of HCV to be five-to tenfold higher in individuals living with an HCV infected person as compared to the general population. Other than sexual contacts, nonsexual risk factors include mother to child exposure at birth and some behavioral attitudes at risk such as sharing of toothbrush, blades, and razors [Ackerman et al, 2000;Akhtar et al, 2002;Memon and Memon, 2002;Mast, 2004]. Other reports, in contrast, suggested a very low extent for intrafamilial transmission of HCV [Kim et al, 1998;Saltoglu et al, 1998;Keiserman et al, 2003].…”
Section: Discussionmentioning
confidence: 99%
“…48 Conversely, a cross-sectional study performed in Pakistan found that 20.5% of 341 household contacts of 86 anti-HCV-positive children with thalassemia had anti-HCV antibodies. 49 In another study, performed in India, 16% of 125 first-degree relatives of thalassemia patients with chronic HCV infection were found to be positive for anti-HCV. 50 The high number of successful pregnancies has provided evidence of the relative safety of pregnancy in women with thalassemia major.…”
Section: What Proportion Of Thalassemia Patients Have Chronic Viral Imentioning
confidence: 97%
“…In this age group 38% patients have higher level of Bilirubin (2.6 ± 11) while, 45% have higher level of Alakaline phosphtase (370 ± 56) as compare to the normal limits (Figures 1-2). Many of the earlier studies from various regions of Pakistan have reported high prevalence of HCV (20.5% -60%), [9,10]. The poor dental procedures are the major source of HBV or HCV exposure (39.7%) that is followed by injections (16.6%) and finally the surgical unsterilized items (16.6%) [11].…”
Section: Group 4 (Female Above Age 35 Years)mentioning
confidence: 99%